Single nucleotide polymorphisms in MBL1 gene of cattle and their association with milk production traits and somatic cell score - BAGHEL, MANALI; SHARMA, DEEPAK; SINGH, SATYENDRA P; TIWARI, MADHU; KUMAR, AVNEESH (The Indian Journal of Animal Sciences, 2025)
Mannose-binding lectin (MBL), a pattern recognition molecule, is an important component of innate immune system. With multiple carbohydrate-recognition domains, it is able to bind to sugar groups present on the surfaces of a wide range of microorganisms and thereby provide first-line defence. MBL gene possibly contributes to bacterial infection resistance and was proposed as a molecular marker for milk production traits to control mastitis. A total of 100 cows (Hariana and Sahiwal) in milk were randomly selected and screened for the presence of one reported SNP (g.855G>A) in intron I and two SNPs (g.2686T>C and g.2651G>A) in exon 2 region of MBL1 gene. A 588 bp PCR fragment encompassing the intron I as well as 401 and 162 bp of containing the exon 2 of MBL1 gene were amplified and digested with ApaI, HaeIII and StyI, respectively. Genotype analysis using PCR-RFLP revealed a polymorphic banding pattern for g.855G>A and g.2686T>C while a monomorphic pattern for g.2651G>A. Association study of observed genotypes with milk production traits and somatic cell score (SCS) revealed a significant difference among g.2686T>C genotypes with age at first calving and SCS in Hariana cattle only. Although, the association study in present work was based on a relatively small sample size, further studies with large sample size are required to validate the impact of these SNPs.